(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
All around the media scene in India is that media doesn’t address major issues about misuse and in equal treatment to women in various circles yet is sharp in announcing sex related occurrences via sensationalizing information on abominations on women. Consequently as opposed to featuring the misuse of lady they wind up getting one reason in increment of brutality as their inclusion as a rule will in general laud the crime against women. The facts demonstrate that media has exposed as at no other time certain crimes against women yet in an unpretentious way it additionally sustained the generalized picture of lady as a householder and an immaterial substance in the customary worth framework. For the most part, women’s issues never figure on the first page of a newspaper except if it is a horrifying homicide or an instance of assault. Newspapers even on women’s page don’t ordinarily address important issues for women strengthening yet announcing is worried about magnificence tips plans, style disorder and so.